Expression of TLR2/4 in the sperm‐storing oviduct of the Chinese soft‐shelled turtle Pelodiscus sinensis during hibernation season. Issue 19 (23rd September 2015) - Li, Quanfu; Hu, Lisi; Yang, Ping; Zhang, Qian; Waqas, Yasir; Liu, Tengfei; Zhang, Linli; Wang, Shuai; Chen, Wei; Le, Yuan; Ullah, Shakeeb; Chen, Qiusheng
Abstract The initiation of innate immunology system could play an important role in the aspect of protection for sperms long‐term storage when the sperms got into oviduct of turtles and come into contact with epithelium. The exploration of TLR2/4 distribution and expression in oviduct during hibernation could help make the storage mechanism understandable. The objective of this study was to examine the gene and protein expression profiles in Chinese soft‐shelled turtle during hibernation from November to April in the next year. The protein distribution of TLR2/4 was investigated in the magnum, isthmus, uterus, and vagina of the turtle oviduct using immunohistochemistry, and the gene expression of TLR2/4 was analyzed using quantitative real‐time PCR (qRT‐PCR). The results showed positive TLR2 protein expression primarily in the epithelium of the oviduct. TLR4 immunoreactivity was widely observed in almost every part of the oviduct, particularly in the epithelium and secretory gland membrane. Analysis of protein, mRNA expression revealed the decreased expression of TLR2/4 in the magnum compared with the isthmus, uterus, and vagina during hibernation. The protein and mRNA expression of TLR2 in the magnum, isthmus, uterus, and vagina was decreased in April compared with that in November. TLR4 protein and mRNA expression in the magnum, isthmus, uterus and vagina was decreased in November compared with that in April. These results indicated that TLR2/4 expression might protect the sperm from microbial infections. In contrast to the function of TLR2, which protects sperm during the early stages of hibernation, TLR4 might play a role in later stages of storage. The present study is the first to report the functions of TLR2/4 in reptiles.